ANALISIS KOMPOSISI FOTOGRAFI PADA FOTO ‘LANDSCAPE’ KARYA NADAV KANDER - Chika Maulidya; Tulus Rega Wahyuni E (UNIVERSITAS NUSA PUTRA, 2022)
This study aims to describe the composition used to convey messages in landscape photography by Nadav Kander. Landscape is a photo position with a horizontal orientation and referring to the landscape, landscape is an aspect of spatial planning such as the use of land area and division of areas. In each of Nadav Kander’s works, he is dominated by the use of high angle and low angle viewpoints, natural lighting, the layout used varies from the rule of thirds, symmetrical, diagonal, and leading line and combines colors well so that the work he makes can be perceived aesthetics as well as the message to be conveyed from each of his works. This type of research is descriptive qualitative research with data obtained by observation and documentation. There are 5 landscape photography works by Nadav Kander which are analysed by describing the work, describing the composition contained in the work. The result of the study show that all the photographic compositions used by Nadav Kander convey the message of life and object from Tiongkok by considering the composition of each of Nadav Kander’s works.